A Constitutive Model of Sandy Gravel Soil under Large-Sized Loading/Unloading Triaxial Tests. (14th June 2021) - Zhang, Pengfei; Liu, Han; Feng, Zhentu; Jia, Chaofeng; Zhou, Rui
Abstract : Based on large-scale triaxial tests of sandy gravel materials, the strength and deformation characteristics under loading/unloading conditions are analyzed. At the same time, the applicability of the hyperbolic constitutive model to sandy gravel is studied using experimental data. The results indicate that sandy gravel under low confining pressures (0.2 and 0.4 MPa) shows a weak softening trend; the higher the confining pressure, the more obvious the hardening tendency (0.6 and 0.8 MPa) and the greater the peak strength. During unloading tests, strain softening occurs, and the peak strength increases with increasing confining pressure. During loading tests, dilatancy appears when the confining pressure is low (0.2 MPa). With increasing confining pressure (0.4, 0.6, and 0.8 MPa), the dilatancy trend gradually weakens, and the cumulative volume tric strain increases, which reflects the relevance of the stress paths. Through research, it is found that the hyperbolic constitutive model has good applicability to sandy gravel soils, and the corresponding model parameters are obtained.